Contextual Teaching Learning pada Pembelajaran Pendidikan Agama Kristen sebagai Strategi mencapai Pengalam Spiritual - Zai, Yafarman; Larosa, Setiaman (MANTHANO: Jurnal Pendidikan Kristen, 2024)
Abstract: In Christian Religious Education learning, intellectual theory and spiritual experience are two concepts that must be achieved. Both are specifically related to each other and differentiate them from other lessons. Achieving both is not easy if done with the wrong strategy. Many problems were found that students felt that PAK lessons were very boring, seemed theoretical and did not build spiritual experiences for their students. The author examines that CTL is the right strategy to answer this problem. Contextual Teaching Learning (CTL) is a learning strategy that connects what is learned with real life, with an emphasis on cognitive development and students' learning experiences as well as their ability to apply knowledge in everyday life. By using the literature study method by conducting a literature review related to the CTL concept, the results were found that CTL has implementation steps, namely: constructivism, inquiry, questioning, community learning, modeling, reflection, and authentic assessment where experience is a characteristic of each of these steps.. The application of CTL in PAK will train students to have a spiritual experience with God and be able to live in their knowledge of Christ. So, CTL can help Christian Religious Education educators carry out a learning process that is not only fun but also builds students' spirituality based on the spiritual experiences they experience while studying Christian religious lessons.  Abstrak: Dalam pembelajaran Pendidikan agama Kristen, teori intelektual dan pengalaman spiritual adalah dua konsep yang harus dicapai. Keduanya saling berkaitan secara spesifik dan menjadi pembeda dari pelajaran lainnya. Pencapaian keduanya tidaklah mudah jika dilakukan dengan strategi yang keliru. Banyak masalah ditemukan bahwa peserta didik merasa pelajaran PAK sangat membosankan, terkesan teoritis dan tidak membangun pengalaman spiritual bagi peserta didiknya. Penulis meneliti bahwa CTL merupakan strategi yang tepat untuk menjawab persoalan tersebut. Contextual Teaching Learning (CTL) adalah strategi pembelajaran yang menghubungkan apa yang dipelajari dengan kehidupan nyata, dengan penekanan pada perkembangan kognitif dan pengalaman belajar peserta didik serta kemampuan mereka untuk menerapkan pengetahuan dalam kehidupan sehari-hari. Dengan menggunakan metode studi literatur dengan melakukan kajian pustaka terkait konsep CTL, maka ditemukan hasil bahwa CTL memiliki langkah penerapan, yaitu: konstruktivisme, inquiry, questioning, community learning, modelling, reflection, dan authentic assessment yang mana pengalaman menjadi suatu ciri khas setiap langkah tersebut. Penerapan CTL dalam PAK akan melatih peserta didik untuk mempunyai pengalaman spiritual dengan Tuhan dan mampu hidup dalam pengenalan mereka kepada Kristus. Jadi, CTL dapat membantu para pendidik Pendidikan Agama Kristen melaksanakan proses pembelajaran yang bukan hanya menyenangkan tetapi juga membangun spiritual peserta didik berdasarkan pengalaman spiritual yang dialaminya saat belajar pelajaran agama Kristen.